2013
DOI: 10.1007/s12040-013-0292-0
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of topographic index in relation to terrain roughness and DEM grid spacing

Abstract: Topographic index is an important attribute of digital elevation model (DEM) which indicates soil saturation. It is used for estimation of runoff , soil moisture, depth of ground water and hydrological simulation. Topographic index is derived from DEMs; hence the accuracy of DEM influences its computation. Commonly the raster based grid DEM is widely used to simulate hydrological model parameter, and accuracy varies with respect to DEM grid size and morphological characteristics of terrain. In this study topog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(29 citation statements)
references
References 50 publications
0
29
0
Order By: Relevance
“…In this study, the TRI was used as the amount of elevation difference among the adjacent cells of a DEM (Mukherjee et al, 2013b). The residuals in elevation between a grid cell and its eight neighbors were derived, and the RMSE of the elevation differences was calculated as the TRI.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, the TRI was used as the amount of elevation difference among the adjacent cells of a DEM (Mukherjee et al, 2013b). The residuals in elevation between a grid cell and its eight neighbors were derived, and the RMSE of the elevation differences was calculated as the TRI.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, second-order finite difference was used. Four Closest Neighbours (FCN) algorithm (Guth 1995;Raaflaub and Collins 2006;Mukherjee et al 2013a) was used for computing slope. It takes into account two orthogonal components of slope in x and y direction.…”
Section: Calculation Of Slopementioning
confidence: 99%
“…Like any spatial dataset, DEMs are also subjected to different types of error (Rodgriguez et al 2006), deficient orientation of stereo images (systematic error) when photogrammetrically determining elevation values (Mukherjee et al 2011), and some unknown combinations of errors (random error) which cannot be avoided. The other issues related to DEM accuracy are grid spacing and interpolation techniques (Mukherjee et al 2013a).…”
Section: Introductionmentioning
confidence: 99%
“…Several researchers have concluded that the DEM grid size influences the slope gradient and slope length factors (Gao 1997;Lin et al 2013;Mukherjee et al 2013). The average of slope gradient decreased with increasing DEM grid size (Gao 1997;David and McCabe 2000;Thompson et al 2001;Wang and Wang 2009).…”
Section: Introductionmentioning
confidence: 99%